Forensic efficiency parameters for the 15 STR loci in the population of the island of Cres (Croatia) - Novokmet, Natalija (Array, 2009)
Abstract: Forensic parameters based on 15 AmpFlSTR Identifiler short tandem repeat (STR) loci (D8S1179, D21S11, D7S820, CSF1PO, D3S1358, TH01, D13S317, D16S539, D2S1338, D19S433, VWA, TPOX, D18S51, D5S818 and FGA) were evaluated in the sample of 122 unrelated, autochthonous, adult individuals from the Island of Cres (Croatia). PCR amplification was performed with the AmpFlSTR Identifiler PCR Amplification Kit and the amplified products were separated and detected using the ABI 3130 DNA genetic analyzer. The agreement with Hardy Weinberg Equilibrium (HWE) was confirmed for all loci (p>0.05). The combined power of discrimination (PD) and the combined power of exclusion (PE) for the 15 tested STR loci were 0.99999999999999997988728679 and 0.999997397, respectively. According to the presented data, D18S51 proved to be the most informative marker followed by markers D2S1338 and D21S11. Interpopulation comparisons in allele frequencies with other East Adriatic Islands revealed significant differences for all analyzed population pairs ranging from 4 loci (Cres vs. Hvar) to 1 locus (Cres vs. Krk). Furthermore, allele frequencies comparisons of Cres and Croatian mainland revealed the lack of statistically significant differences at all studied loci. The results of the current study indicate that the examined fifteen STR loci are useful genetic markers for individual identification and paternity testing in Croatian population from the Island of Cres